IMPLICATURE IN TOY STORY : UNVEILING THE IMPLIED BEHIND MAIN CHARACTER UTTERANCES - Umami, Sherly Zahira; Nadita , Faradina Juninda (ELite Journal : International Journal of Education, Language and Literature, 2025)
"Toy Story," Pixar's pioneering animated film, combines groundbreaking computer animation with a rich narrative that explores complex character dynamics and moral lessons. Focusing on Woody, the cowboy protagonist, the film uses his dialogues to subtly convey deeper meanings, emotions, and moral values through implicature. Woody's conversations, analyzed through Paul Grice's conversational theory, reveal a mix of dominant, manipulative, and vulnerable traits that reflect his internal conflicts and insecurities. These dialogues, which sometimes violate conversational maxims of quantity, quality, relevance, and manner, serve as a vehicle for communicating underlying messages. For instance, Woody's incomplete information and indirect remarks about Buzz Lightyear imply his jealousy and fear of losing Andy’s favor. His guilt and struggle to maintain a leader's image are subtly hinted through his deceptive honesty and ambiguous language. The film's portrayal of Woody’s evolving relationship with Buzz from rivalry to friendship underscores themes of self-acceptance and trust. This study demonstrates how animated films like "Toy Story" can effectively convey moral lessons through implicit communication, enhancing the emotional impact without overtly stating the messages.